2009
DOI: 10.1017/s1049023x00006610
|View full text |Cite
|
Sign up to set email alerts
|

First Responders after Disasters: A Review of Stress Reactions, At-Risk, Vulnerability, and Resilience Factors

Abstract: Disasters are widely reported, commonplace events that characteristically leave an enormous legacy of human suffering through death, injury, extensive infrastructural damage, and disorganization to systems and communities.The economic costs may be almost incalculable. Professional and civilian first responders play a vital role in mitigating these effects. However, to maximize their potential with the minimum health and welfare costs to first responders, is important to have a good understanding of the demands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 68 publications
(41 reference statements)
3
84
0
1
Order By: Relevance
“…Police officers are exposed to traumatic events during their careers (Weiss et al, 2010) that may impair their ability to function normally (Alexander & Klein, 2009). Continued avoidance of treatment can cause problems at work and at home, termination of Police Practice and Research: An International Journal 7 employment, and sometimes, in worse-case scenarios, suicide (Barron, 2010;Bloodgood, 2006;Chae & Boyle, 2013;Larned, 2010;McCafferty, McCafferty, & McCafferty, 1992;Perin, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Police officers are exposed to traumatic events during their careers (Weiss et al, 2010) that may impair their ability to function normally (Alexander & Klein, 2009). Continued avoidance of treatment can cause problems at work and at home, termination of Police Practice and Research: An International Journal 7 employment, and sometimes, in worse-case scenarios, suicide (Barron, 2010;Bloodgood, 2006;Chae & Boyle, 2013;Larned, 2010;McCafferty, McCafferty, & McCafferty, 1992;Perin, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they are often exposed to traumatic events that produce emotional and cognitive reactions and potentially debilitate normal functioning in daily roles and responsibilities (Alexander & Klein, 2009;Collins & Gibbs, 2003). As reported in Perrin et al (2007), the US' national prevalence of Post-Traumatic Stress Disorder (PTSD) is roughly 4%; however, for first responders, these levels range from 5 to 36% (Bloodgood, 2006;Carlier, Lamberts, Van Uchelen, & Gersons, 1998;Centers for Disease Control, 2004;Kleim & Westphal, 2012;Norris, Tracy, & Galea, 2009;Robbers & Jenkins, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that these professionals have the highest occupational fatality rates in the U.S., mainly due to cardiovascular problems [1]. These problems can result from the long time exposures to several traumatic, non-traumatic, and organizational stressors over time [2], which are known to be associated with psychological and physical illness [3]. This motivates the need for new systems and technologies capable of monitoring, in real time, the physiological signals and the behaviour patterns of these professionals, in order to assess their stress levels.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, many responders report positive impacts of their work during disasters, especially the development of resilience. Frontline healthcare workers have reported that their work during an outbreak had positive impacts through opportunities to reassess their life values and priorities, and deepen their relationships with co-workers and others (Alexander & Klein, 2009). Similarly, many who stayed to fight Ebola within their local communities, or who left home to serve in Ebola regions, reported some positive experiences (von Drehle, 2014).…”
Section: Introductionmentioning
confidence: 99%